Changing it up: implications of mid-season coach change on basketball players` career and professional identities - Purdy, L. G.; Kohe, G. Z.; Paulauskas, R. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Career and professional identities are utilized as a conceptual framework to consider the complexities of basketball players` working lives amidst mid-season coach change. Seven male professional basketball players, working in top European leagues, participated in semi-structured interviews. The interviews were centred on career trajectories and incidents of mid-season coach change. Results indicate sports workers` career success is contingent upon strategically undertaking identity work in order to best respond to the demands of the organizational context. Players` experiences of coach turnover, for example, may have varied however, the event had discernible influence on how they understood themselves, their positional relationship and overall longevity in the sport. Of concern is the necessity for organizations to appreciate their roles in shaping the settings in which their employees work, and the related consequences that contextual changes have in worker`s abilities to labour and the strategies they may need to utilize to cope with such change.